SUSTAINABLE LAND DEVELOPMENT FROM A LEGAL PERSPECTIVE: A CASE STUDY OF INFRASTRUCTURE PROJECTS IN INDONESIA - Gloria Gita Putri Ginting; Muhammad Juang Rambe (RADJA PUBLIKA, 2024)
Infrastructure development in Indonesia often involves complex land issues, including ownership conflicts, land acquisition, and socio-economic impacts on local communities. This study aims to analyze the sustainability of land development from a legal perspective through case studies of infrastructure projects in Indonesia. The methods used are normative and descriptive studies, reviewing laws and regulations, project documents, and related literature. The analysis shows that sustainable land development requires regulatory harmonization, legal certainty for landowners, and fair compensation mechanisms. Weaknesses in legal implementation, complicated administrative procedures, and lack of community participation have the potential to give rise to disputes and delay project implementation. This study emphasizes the importance of integrating legal principles with development planning, including the protection of community rights, transparency, and accountability of relevant institutions. With an effective legal approach, infrastructure projects can be sustainable, reduce land conflicts, and increase socio-economic benefits for communities. These findings provide recommendations for strengthening land regulations, clarifying land acquisition procedures, and improving inter-agency coordination so that infrastructure development can align with the principles of sustainability and legal certainty in Indonesia.